There may be a differential mechanistic impact on colorectal cancer of lactose-containing foods between lactase persistent and lactase non-persistent populations - Szilagyi, Andrew; Galiatsatos, Polymnia; Margolese, Noah (Frontiers in Nutrition, 2026)
It is generally suggested that milk and milk products reduce the risk of colorectal cancer (CRC). While there is some controversy over specific sites affected throughout the colon and the benefits of specific dairy foods (DFs), there is a general consensus that calcium intake is the main mechanism of the cancer-reducing effects. This opinion may be sidelined by several other mechanisms. There is also a potentially important compensatory mechanism in populations with adult genetic lactase deficiency. The microbiome changes occur through a process of adaptation to continued lactose consumption. The bacterial blooms consist largely of Bifidobacterial species. These bacteria may exert anti-neoplastic effects and also increase the capacity of persons with adapted lactase insufficiency to consume dairy products. Bacterial metabolism thus provides a second pathway for lactose digestion. Since the use of Mendelian randomization (MR) accuracy disallow two different pathways for the genetic variable, this process constitutes a horizontal pleiotropy. This narrative review using articles from PubMed and Google Scholar will discuss different nutrients and mechanisms in milk and milk products that are involved in anti-neoplastic effects. The impact of adult lactase deficiency and continued dairy consumption on the microbiome, and its contribution to colorectal cancer reduction, is highlighted. The conclusions from this review are that calcium has multifaceted mechanisms of anti-carcinogenesis, but other nutrients, such as conjugated linoleic acid (CLA), lactoferrin, and folate in the dairy matrix, could also contribute. In lactase non-persistent (LNP) populations adapted to dairy foods, a bifidogenic bloom in the microbiome may add additional anti-neoplastic effects and /or increase dairy food consumption. We argue that predictions of colon cancer effects from dairy foods may be inaccurate, and that evaluating both populations together may confound outcomes.